Effects of ionic strength on lateral particle migration in shear-thinning xanthan gum solutions - Cho, Mira; Hong, Sun Ok; Lee, Seung Hak; Hyun, Kyu; Kim, Ju Min (Micromachines, 2019)
Viscoelastic fluids, including particulate systems, are found in various biological and industrial systems including blood flow, food, cosmetics, and electronic materials. Particles suspended in viscoelastic fluids such as polymer solutions migrate laterally, forming spatially segregated streams in pressure-driven flow. Viscoelastic particle migration was recently applied to microfluidic technologies including particle counting and sorting and the micromechanical measurement of living cells. Understanding the effects on equilibrium particle positions of rheological properties of suspending viscoelastic fluid is essential for designing microfluidic applications. It has been considered that the shear-thinning behavior of viscoelastic fluid is a critical factor in determining the equilibrium particle positions. This work presents the lateral particle migration in two different xanthan gum-based viscoelastic fluids with similar shear-thinning viscosities and the linear viscoelastic properties. The flexibility and contour length of the xanthan gum molecules were tuned by varying the ionic strength of the solvent. Particles suspended in flexible and short xanthan gum solution, dissolved at high ionic strength, migrated toward the corners in a square channel, whereas particles in the rigid and long xanthan gum solutions in deionized water migrated toward the centerline. This work suggests that the structural properties of polymer molecules play significant roles in determining the equilibrium positions in shear-thinning fluids, despite similar bulk rheological properties. The current results are expected to be used in a wide range of applications such as cell counting and sorting.
Keywords: Cell counting; Equilibrium positions; Micro fluidic applications; Microfluidic technologies; Particle focusing; Pressure-driven flows; Shear thinning fluids; Shear-thinning behavior; Cell counting and sorting; Microfluidics; Particle focusing; Shear-thinning; Viscoelasticity; Xanthan gum